2021
DOI: 10.1210/jendso/bvab048.1199
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic Hypophysitis

Abstract: Introduction: Hypophysitis is a heterogeneous condition that leads to inflammation of the sella / suprasellar region, potentially resulting in hormonal deficiencies or mass effects. Prevalence of hypophysitis ranges from 0.2% to 0.88%. Annual incidence of hypophysitis is 1 case per 9 million individuals. We present an interesting case of idiopathic hypophysitis. Clinical Case: A 52-year-old female was evaluated for secondary hypothyroidism. Patient complained of excess fatigue, weight gain, headaches, polyuria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…Many literature have reported that metal oxides catalyst has capability to increase the generation of charge carriers as the band gap decreases [28]. For example, doping Ag metal with ZnO helps in increase the efficiency of degradation from 13% to 91% [29]. Also, by having a narrow band gap which is 3.24 eV, ZnO capable to increase the rate of photocatalytic activity compared to SnO2 that has wide band gap at 3.64 eV.…”
Section: Thermal Evaporationmentioning
confidence: 99%
“…Many literature have reported that metal oxides catalyst has capability to increase the generation of charge carriers as the band gap decreases [28]. For example, doping Ag metal with ZnO helps in increase the efficiency of degradation from 13% to 91% [29]. Also, by having a narrow band gap which is 3.24 eV, ZnO capable to increase the rate of photocatalytic activity compared to SnO2 that has wide band gap at 3.64 eV.…”
Section: Thermal Evaporationmentioning
confidence: 99%